2018
DOI: 10.3390/ijms19082438
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin 2/RXFP1 Signaling Induces Cell Invasion via the β-Catenin Pathway in Endometrial Cancer

Abstract: Relaxin is known to play an important role in animal pregnancies, including those of humans. It is suggested that relaxin induces aggressive cell growth and invasiveness in several types of cancer, including endometrial cancer. However, the mechanisms of relaxin remain largely unclear. In this study, we examined the effects of relaxin 2 (RLN2), the major circulating relaxin in humans, on human endometrial carcinoma cell lines. RLN2 treatment induced invasion in HEC-1B and Ishikawa cells. RLN2-induced cell inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Suppression of RXFP1 inhibits prostate cancer tumorigenesis, growth, and metastasis [4143]. Relaxin 2/RXFP1 Signalling induces cell invasion via the beta-catenin pathway in endometrial cancer [44]. Expression of RXFP1 is decreased in idiopathic pulmonary fibrosis [45] and mediates the effects of miR-144-3p in lung fibroblasts from patients with idiopathic pulmonary fibrosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of RXFP1 inhibits prostate cancer tumorigenesis, growth, and metastasis [4143]. Relaxin 2/RXFP1 Signalling induces cell invasion via the beta-catenin pathway in endometrial cancer [44]. Expression of RXFP1 is decreased in idiopathic pulmonary fibrosis [45] and mediates the effects of miR-144-3p in lung fibroblasts from patients with idiopathic pulmonary fibrosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that relaxin induces aggressive cell growth and invasiveness in several types of cancer, including endometrial cancer. Adherens junctions in cancer cells are weakened by the breakdown of the cadherin/catenin complex, which is induced by β‐catenin phosphorylation via RLN2/RXFP1 signaling . RXFP3 has not been reported and further studies are warranted to clarify the role of RXFP3 in cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the gene RXFP2 that is predicted only in Subtype-2 is found to be involved in neuroactive ligand-receptor interaction. RXFP2 is also found to be involved in Relaxin signaling which induces cell invasion and is reported in several cancers 30 . The modulators of ABC transporters is reported to have the potential to augment the efficacy of anticancer drugs 31 .…”
Section: Discussionmentioning
confidence: 95%